Analysis of Facilities and Power Competency on Implementation of Safety and Health Work in Puskesmas District of Tulungagung - Siswanto Siswanto (Journal for Quality in Public Health, 2018)
Occupational health services shall be an effort to provide occupational health and safety protection to workers' communities, which have the objective of maintaining and improving the health status of the working-class community, Preventing the occurrence of health problems and protecting workers from health hazards and placing workers in the work environment in accordance with their physical and psychological abilities workers. Objective Analysis research is to analyze the completeness of facilities, workforce competencies to the implementation of Occupational Health and Safety in Puskesmas District of Tulungagung. The design used in the study was cross-sectional. The population is Puskesmas District of Tulungagung. The sample size was 32 respondents Health Center by using simple random sampling technique. Independent research variables are Infrastructure and Labor Competencies. The dependent variable is the implementation of Safety Management. Data was collected using kuesoner, then the data were analyzed using linear regression test with a significance level of α ≤ 0.05. The results showed more than half of the health center has the facilities and infrastructure K3 (Occupational Health and Safety Management) is complete as many as 23 respondent’s health centers (76.7%), more than half Puskesmas. as having the competence K3 Officers who are not trained as much as 23 respondents health centers (76.7%). more than half of Puskesmas.have health and safety management that less as much as 19 respondent of health center (63,3%). The result of statistical test shows that there is no influence between K3 infrastructure and worker with K3 management (0,340). The result of statistic test obtained by Pseudo R square value at Nagelkerke is 0,086, which means infrastructure and competence in explaining MK3 implementation is 0,086 (8,6%) and there are 91,4% other factors outside model in implementation of safety and health management MK3).The conclusion of this study is that occupational health safety management can be influenced by many factors. All the supporting factors in the implementation of occupational health safety management should be synergized to achieve optimal work safety objectives.